Sea Ice Elevation in the Western Weddell Sea, Antarctica: Observations From Field Campaign - Huang, Lanqing; id_orcid:0 000-0002-5180-7491; Hajnsek, Irena; id_orcid:0 000-0002-0926-3283; Nghiem, Son V. (American Geophysical Union, 2022)
Sea ice elevation is crucial in the characterization of three-dimensional (3D) sea ice patterns, providing physical insights to advance sea ice dynamic models. Moreover, how sea ice elevation may be related to the ocean geophysical environment is still a significant knowledge gap, especially in Antarctica. A radar theory relating electromagnetic scattering mechanisms to sea ice elevation over old and deformed rough ice has been reported in a prior companion paper. This follow-up paper presents the validated model function and synthetic aperture radar (SAR)-retrieved sea ice elevations based on the field data acquired during the Operation IceBridge and TanDEM-X Antarctic Science Campaign. A high-resolution sea ice digital elevation model (DEM) is generated extensively over a 19 x 450 km sector in the Western Weddell Sea, achieving a good accuracy with a low root-mean-square error of 0.23 m. From the SAR-retrieved sea ice DEM, 3D sea ice patterns including roughness height, auto-correlation lengths, correlation ellipticity, and orientation angles are calculated over the old and deformed rough sea ice. The 3D sea ice patterns give a comprehensive characterization of sea ice topography in the Western Weddell Sea and show the potential to be used for understanding sea ice formation processes in the Antarctic. ISSN:2333-5084